2017
DOI: 10.1002/adfm.201700605
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Cup‐Shaped Nanocrystal with Ultrahigh Photothermal Efficiency as Tumor Therapeutic Agent

Abstract: As an emerging treatment for cancer, phototherapy has received much clinical attention. Here, a multifunctional Au nanocup (Au NC) for the targeted computed tomographic and photoacoustic imaging of cancerous tumors and phototherapy is reported. The Au NC has an intrinsic photothermal conversion efficiency of 38.5% and offers a tumor-specific targeted computed tomographic and photoacoustic imaging system. Furthermore, when treated with nontoxic Au NC-Ce6, cancer cells and tumors are obliterated with low doses o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 60 publications
1
44
0
Order By: Relevance
“…[19] Nanomaterials have great potential for cancer diagnosis [20,21] and therapy. [22][23][24][25][26] As one of the most widely used nanomaterials, silver nanoparticles (Ag NPs) have been proved to be effective in tumor treatment. [27][28][29] We previously reported that Ag NPs-induced cytoprotective autophagy and inhibition of autophagy by chemical inhibitors or ATG5 siRNA enhanced the antitumor effect of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Nanomaterials have great potential for cancer diagnosis [20,21] and therapy. [22][23][24][25][26] As one of the most widely used nanomaterials, silver nanoparticles (Ag NPs) have been proved to be effective in tumor treatment. [27][28][29] We previously reported that Ag NPs-induced cytoprotective autophagy and inhibition of autophagy by chemical inhibitors or ATG5 siRNA enhanced the antitumor effect of Ag NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Reduced graphene-based drug-delivery systems have attracted the most attention because of their unique physical, electrical and chemicalp roperties, andt hey have been widely used as biomedical treatments, particularly for use in photothermal therapy( PTT) and cell imaging. [11][12][13][14][15][16][17][18][19][20][21][22] PTT is one of the mostp rominentm ethods for the application of rGO-based nanodrug systems. [23] Compared with traditional chemotherapy,P TT takes advantages of direct heatingo ft he cancerc ellsa nd results in minimal damaget os urrounding tissue.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo photothermal therapy showed great tumor growth inhibition efficacy by one‐time irradiation of NIR laser after a single injection of these multidentate PEG‐modified AuNRs . Xu and co‐workers reported a multifunctional PEG‐modified Au nanocup, with unique photothermal conversion efficiency, which could efficiently eliminate tumor tissues both in vitro and in vivo . Furthermore, PEGylation on AuNPs could also be beneficial for photodynamic therapy (PDT).…”
Section: Applicationmentioning
confidence: 99%